Dreams, race, and the black lives matter movement: results of a survey of American adults - Bulkeley, Kelly; Schredl, Michael (Pastoral psychology, 2022)
This study considers the relationship between dreaming and race in light of the public protests following the murder of George Floyd on May 25, 2020. Findings are presented from an online survey about dreams and the Black Lives Movement (BLM) gathered from 4,947 demographically diverse American adults sampled between June 15 and June 19, 2020. The results show that the people most likely to have dreams about the public protests were those who support BLM, who are highly educated, and/or who have high dream recall. The dreams themselves tended to be anxious, fearful, and nightmarish, with several recurrent themes: references to George Floyd, participating in protests, threats to one’s home, concerns about the pandemic, and conversations about BLM. The findings of this study contribute to a growing research literature showing that dreams, dream recall, and dream sharing can vary significantly depending on people’s racial, ethnic, and cultural backgrounds. This study also provides new evidence that dreams have meaningful content relating directly to current events and public affairs. Practical implications for therapists and pastoral counselors are discussed.